Down-regulation of KCa2.3 channels causes erectile dysfunction in mice - Simon Comerma-Steffensen (Nature Portfolio, 2017)
Abstract Modulation of endothelial calcium-activated K+ channels has been proposed as an approach to restore arterial endothelial cell function in disease. We hypothesized that small-conductance calcium-activated K+ channels (KCa2.3 or SK3) contributes to erectile function. The research was performed in transgenic mice with overexpression (KCa2.3 T/T(−Dox)) or down-regulation (KCa2.3 T/T(+Dox)) of the KCa2.3 channels and wild-type C57BL/6-mice (WT). QPCR revealed that KCa2.3 and KCa1.1 channels were the most abundant in mouse corpus cavernosum. KCa2.3 channels were found by immunoreactivity and electron microscopy in the apical-lateral membrane of endothelial cells in the corpus cavernosum. Norepinephrine contraction was enhanced in the corpus cavernosum of KCa2.3 T/T(+Dox) versus KCa2.3 T/T(−Dox) mice, while acetylcholine relaxation was only reduced at 0.3 µM and relaxations in response to the nitric oxide donor sodium nitroprusside were unaltered. An opener of KCa2 channels, NS309 induced concentration-dependent relaxations of corpus cavernosum. Mean arterial pressure was lower in KCa2.3 T/T(−Dox) mice compared with WT and KCa2.3 T/T(+Dox) mice. In anesthetized mice, cavernous nerve stimulation augmented in frequency/voltage dependent manner erectile function being lower in KCa2.3 T/T(+Dox) mice at low frequencies. Our findings suggest that down-regulation of KCa2.3 channels contributes to erectile dysfunction, and that pharmacological activation of KCa2.3 channels may have the potential to restore erectile function.